Impacto de la exposición de las redes sociales sobre Ansiedad y Depresión en estudiantes de medicina durante la pandemia COVID-19 - Villacorta Rodríguez, Javier Asencio (2022)
To determine the impact of the exposure of social networks on Anxiety and Depression in students from first to sixth year of the Faculty of Medicine of the National University of Trujillo during the COVID-19 pandemic. Methods: A cross-sectional retrospective analytical research was carried out. The study population comprised 172 medical students from 1st to 6th year. An anonymous survey consisting of 4 sections, demographic data, the frequency of exposure to social networks, the Patient Health Questionnaire (PHQ-9) to evaluate the level of depression and the Generalized Anxiety Disorder Scale (GAD-7) was applied. to assess the level of anxiety. The data were analyzed using simple and crossed tables with simple and percentage frequencies. In addition, Kendall's Tau-b test was used to determine the association between the level of exposure to social networks and depression; and Kendall's Tau-c to determine the association between the level of exposure to social networks and anxiety. Results: 98.3% were exposed at some level of frequency to social networks with information about the COVID-19 pandemic. It shows a prevalence of 65.1% and 47.7% of medical students with levels of depression and anxiety respectively, of which 23.8% with depression and 12.8% with anxiety with levels equal to or greater than moderate levels. According to Kendall's Tau-b test = 0.023 (p = 0.744), a value very close to zero, which means that there is little relationship between the depression variable and exposure to social networks. Meanwhile, Kendall's Tau-c correlation coefficient = 0.016 (p = 0.8), a value close to zero, which indicates that there is little relationship between the anxiety variable and exposure to social networks. Conclusions: There are not enough reasons to affirm that the level of exposure to social networks is related to the level of anxiety and depression.